2017
DOI: 10.1098/rspb.2017.0324
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for parallel evolution of a gene involved in the regulation of spermatogenesis

Abstract: () is a male germline specific gene in that can trigger the male germline sexual fate and regulate spermatogenesis, and its human homologue can rescue fecundity defects in male flies lacking this gene. These findings prompted us to investigate conservation of reproductive strategies through studying the evolutionary origin of this gene. We find that is present only in select species including mammals and some insects, whereas the closely related () is in the genome of most metazoans. Interestingly, phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The cause for such gender disparities remains unknown. Homologs of Drosophila Phf7 have been identified in vertebrates including mammals, and human Phf7 expression is also highly enriched in the testis ( 42 , 43 , but there is currently no evidence suggesting a role for Phf7 in sex dimorphism in human cancer. Despite substantial sequence homology, human Phf7 and Drosophila Phf7 did not evolve from a common Phf7 ancestor, but rather, both genes evolved in parallel through independent duplication events from an ancestral G 2 -M phase–specific E3 ubiquitin protein ligase (G2E3) ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause for such gender disparities remains unknown. Homologs of Drosophila Phf7 have been identified in vertebrates including mammals, and human Phf7 expression is also highly enriched in the testis ( 42 , 43 , but there is currently no evidence suggesting a role for Phf7 in sex dimorphism in human cancer. Despite substantial sequence homology, human Phf7 and Drosophila Phf7 did not evolve from a common Phf7 ancestor, but rather, both genes evolved in parallel through independent duplication events from an ancestral G 2 -M phase–specific E3 ubiquitin protein ligase (G2E3) ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Homologs of Drosophila Phf7 have been identified in vertebrates including mammals, and human Phf7 expression is also highly enriched in the testis ( 42 , 43 , but there is currently no evidence suggesting a role for Phf7 in sex dimorphism in human cancer. Despite substantial sequence homology, human Phf7 and Drosophila Phf7 did not evolve from a common Phf7 ancestor, but rather, both genes evolved in parallel through independent duplication events from an ancestral G 2 -M phase–specific E3 ubiquitin protein ligase (G2E3) ( 42 ). Functional overlap between both homologs is high, but not full: Human Phf7 can rescue the fertility defects brought about by the loss of Phf7 in Drosophila males, but does not have the deleterious effect brought about by the fly protein when expressed in the female germline ( 33 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…PHF7 contains three PHD domains in its N-terminus that presumably mediate its interaction with H3K4me2-modified chromatin, whereas the C-terminus bears no resemblance to any known protein domains. Recently we found that the three PHD domains are sufficient to rescue the fecundity defects of Phf7 mutant male flies (Wang et al 2017). It is possible that upon association of PHF7 with H3K4me2, located at the 59 end of the target gene body, PHF7 inhibits transcription of the target genes by directly blocking access of chromatin remodelers and transcriptional coactivators, or by recruiting transcriptional corepressors.…”
Section: Phf7 Regulates Both Germline Sex Determination and Spermatogmentioning
confidence: 99%
“…The flies used in this study are cultured on standard media. The strains include: w 1118 , Phf7 Δ N2 7 , Phf7 Δ N18 7 , vas-GFP 14 , EY03023, UAS-Phf7-FL 7 , UAS-Phf7-N 10 , UAS-Phf7-C, nos-Gal4 15 , tra 1 , Df(3L)st-j7, HP1D3csd f07323 , UAS-HP1D3csd.ORF.3xHA.GW, Df(1)ED7441, Dp(1:Y)B s , FM7a,Dfd-YFP. Stocks were obtained from the Bloomington Stock Center unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, only amniotes and some insects of Diptera have a Phf7 gene 10 , and Drosophila Phf7 genes are unique in that they contain extended C-termini that do not match any known protein domains. Moreover, this portion of Drosophila Phf7 appears to be rapidly evolving as homology between more distant Drosophila species is already lost.…”
Section: Introductionmentioning
confidence: 99%